Liquid milk: Cash constraints and day-to-day intertemporal choice in financial diaries - Geng, Xin; Janssens, Wendy; Kramer, Berber (2017)
This paper tests whether cash constraints affect preferences over the timing of income, using high-frequency panel data of intertemporal choice among Kenyan dairy farmers. When selling milk, these farmers choose between a cooperative, which defers payments by approximately one month, and the market, which pays upon delivery. Cash constraints could hence induce farmers to obtain relatively more dairy income from the market. Semi-parametric panel data estimates yield robust evidence of this theory. Farmers receive a substantial share of dairy income from the market. This share increases ceteris paribus in weeks with either lower inflows of cash or uninsured health shocks. Further, although the market pays on average less than the cooperative, farmers receive more cash per liter of milk sold in the market when non-dairy income is low. Thus, cash constraints affect preferences over the timing of income, and selling in the market is an important source of cash for dairy farmers. Financial instruments that can help relax cash constraints, for instance better access to advance payments or health insurance, may encourage farmers in need of cash to keep selling to the cooperative, which potentially improves farmers’ loyalty to welfare-enhancing collective marketing arrangements.